DEVELOPMENT OF A CONCENTRATE BASED ON PROTEIN-CARBOHYDRATE RAW MATERIALS - MILK WHEY AND ITS APPLICATION IN THE RECIPE OF AN INNOVATIVE COSMETIC PRODUCT FOR HAIR - M. A. Chikatueva; E. A. Abakumova; M. I. Shramko; A. G. Khramtsov (Современная наука и инновации, 2022)
The problem of the rational use of milk whey has been studied. suggested the use of whey as the main ingredient in the creation of a cosmetic line. Materials and research methods determined. The urgency of obtaining an innovative cosmetic product (shampoo for hair) based on milk whey concentrate has been substantiated. The optimal dosage of the original milk whey for the concentrate has been determined. An experiment was carried out to determine the content of carbohydrates and protein in a fermented mixture of whey and wort. The organoleptic indicators of the quality of the fermented mixture of whey and wort have been studied. The safety indicators of the developed hair shampoo have been determined. The results obtained confirm the possibility of using protein-carbohydrate raw materials, milk whey, in the formulation of an innovative cosmetic product (hair shampoo). Optimized modes for the formation of a concentrate formulation for shampoo from a 6.0% aqueous solution of milk whey. The directed hydrolysis of lactose in a substrate of whey with beer wort, followed by cultivation with yeast and the simultaneous introduction of beer wort into the mixture, was studied. As a result of biotechnological conversion, the content of carbohydrates and protein in the fermented mixture of whey and wort changes. Based on the results of sensing organoleptic samples of whey serum with wort, it was concluded that one of the formed homogeneous consistency, without a pungent smell of beer. The indicators of quality and safety of the developed hair shampoo have been determined. In terms of microbiological, toxicological indicators and the content of toxic elements, the cosmetic product meets the requirements of TR CU 009/2011 "On the safety of perfumery and cosmetic products." The results obtained confirm the possibility of using protein-carbohydrate raw materials - milk whey in innovative cosmetics (hair shampoo).